Optimal-Fair Waste Load Allocation of River System Based on Rawls Theory - Maryam Ostad Mohammadi; Mohammad Hossein Niksokhan; Shervin Jamshidi (Environmental Energy and Economic Research, 2024)
Global attention has focused on the general deterioration of water quality due to rapid industrialization, population growth and a steady decline in the amount of safe water available. This study provides a new framework for waste load allocation from an fair and equitable perspective. First, the optimal scenarios are generated by calling the (Streeter-Phelps) S-P equation with the Nod-dominated Genetic Algorithm-II (NSGA-II) optimization algorithm. In addition, using two fairness measures from Rawls' theory of justice, two optimization problems specifying have been defined with three objective functions, such as minimizing total treatment costs and violating standards. Then the Complex Proportional Assessment (COPRAS) method has been used to select and compare most waste load allocation scenarios. Results indicated that optimal waste load allocation scenarios based on Rawls justice theory in addition to reduce of the violation rate of the DO could effectively configure a system to allocate treatment cost fairly.